Evaluation Of APC Gene Expression And Methylation Pattern Following Bone Marrow-Derived Mesenchymal Stem Cell Differentiation Into Osteoblasts Category - Raja Al-Huthaifi; Ali Dehghanifard; Saeid Kaviani; Mehrdad Noruzinia; Samira Rezaei; Mehdi Azad; Maedeh Mashhadikhan; Saeid Solali (Tehran University of Medical Sciences, 2016)
Background and Aim: Different regulation processes have an effect on osteoblastic differentiation of mesenchymal stem cells (MSCs), and among them Wnt signaling pathway is particularly desirable. In Wnt signaling pathway, Adenomatous Polyposis Coli (APC) bind to β-catenin and induce its degradation, thereby acting as a negative regulator of canonical Wnt pathway. In this study, gene expression and DNA methylation of APC gene during osteoblastic differentiation were determined. Materials and Methods: In this experimental study, after the isolation of MSCs, the induction of osteoblastic differentiation was done. To confirm osteoblastic differentiation, alizarin red staining together with the expression of Alkaline Phosphatase (ALP) and osteocalcin as specific osteoblastic markers was performed. APC gene methylation status by MSP (Methylation Specific PCR) and gene expression status of APC gene using Real-Time PCR technique during different times were evaluated. Results: The results of alizarin red staining and the expression of ALP and osteocalcin confirmed osteoblastic differentiation. In addition, the results showed a significant decrease in the expression of APC gene on the 7th day of osteoblastic differentiation (P<0.05). Also, the results revealed hypermethylation status of APC gene promoter during osteoblastic differentiation. Conclusion: It seems that the decreased expression APC gene will play an important role in Wnt signaling pathway regulation in different stages during osteoblastic differentiation of bone marrow-derived MSC. Also, according to the results, APC gene promoter methylation will play an important role in controlling gene expression.